An unusual presentation of neurobrucellosis with Guillain-Barré syndrome - DR.E.DHIVYA; DR.K.H.NOORUL AMEEN (International Journal of Pharma and Bio Sciences, 2017)
Human brucellosis is an infectious, zoonotic disease that has a varied clinical spectrum of manifestations. Brucellosis is caused by the bacteria belonging to the genus Brucella. Brucellae are gram negative, aerobic coccobacilli which can affect any organ like central nervous system, joints, heart, kidney, skin, pulmonary system and genitourinary system leading to varied clinical symptoms. Neurobrucellosis is relatively rare and serious disease which includes meningoencephalitis, encephalitis, myelitis, subarachnoid hemorrhage, cranial and peripheral neuropathy, and psychiatric manifestations. We report an unusual case of neurobrucellosis presenting with manifestations of Guillain-Barré Syndrome with fever and bilateral lower motor neuron facial palsy. The patient was treated with IV Immunoglobulins and antimicrobial therapy such as doxycycline and rifampin. The patient showed marked clinical improvement. Thus timely diagnosis and effective treatment leads to good resolution of the symptoms and prognosis.